2008
DOI: 10.1021/jf072382z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 3-Alkyl-2-methoxypyrazines in Lady Beetle-Infested Wine by Solid-Phase Microextraction Headspace Sampling

Abstract: This study determined the concentration of 3-alkyl-2-methoxypyrazines in Frontenac and Leon Millot wines made from grapes that were naturally or artificially infested with the multicolored Asian lady beetle, Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae). Headspace sampling with solid-phase microextraction (SPME) and gas chromatography (GC) was used for the quantification of 3-isopropyl-2-methoxypyrazine (IPMP), 3- sec-butyl-2-methoxypyrazine (SBMP), and 3-isobutyl-2-methoxypyrazine (IBMP). The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
(52 reference statements)
2
28
2
Order By: Relevance
“…Therefore, most studies have addressed the management of alkyl methoxypyrazines through viticultural practices (Chapman et al 2004, Sala et al 2004, Falcão et al 2007, with particular emphasis on cluster light interception Samuta 1999, Ryona et al 2008). The exception to this proposition has been in the study of ladybug taint, which is the contribution of 3-isopropyl-2-methoxypyrazine (IPMP), extracted from Harmonia axyridis (Pallas) (Galvan et al 2008), which can increase the peanut, asparagus/bell pepper, and earthy/herbaceous aromas in red wines (Pickering et al 2004).…”
Section: Pyrazinesmentioning
confidence: 99%
“…Therefore, most studies have addressed the management of alkyl methoxypyrazines through viticultural practices (Chapman et al 2004, Sala et al 2004, Falcão et al 2007, with particular emphasis on cluster light interception Samuta 1999, Ryona et al 2008). The exception to this proposition has been in the study of ladybug taint, which is the contribution of 3-isopropyl-2-methoxypyrazine (IPMP), extracted from Harmonia axyridis (Pallas) (Galvan et al 2008), which can increase the peanut, asparagus/bell pepper, and earthy/herbaceous aromas in red wines (Pickering et al 2004).…”
Section: Pyrazinesmentioning
confidence: 99%
“…Galvan et al (2008) analyzed wines produced from Frontenac grapes that had been artificially infested with MALB at levels of one, three and eight live beetles/kg grapes and from Leon Millot grapes harvested from vineyards with two different degrees of 'natural' MALB infestation (20% and 50% of the clusters infested with one or more Harmonia axyridis adults). No differences in concentration of IPMP were found between wines with different infestation levels.…”
Section: Causal Compound(s)mentioning
confidence: 99%
“…Moreover, possible infestations with lady beetles may also contribute MPs to affected wines. In particular, elevated levels of IPMP and SBMP are associated with this phenomenon (Galvan et al, 2008). It has also been reported that bottle closure and packaging type affect MP concentrations during wine storage, with the three major MPs affected to differing degrees.…”
Section: Introductionmentioning
confidence: 94%